PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING (GBL) MENGGUNAKAN MEDIA BAAMBOOZLE TERHADAP MINAT BELAJAR SISWA MTS MUHAMMADIYAH PENYASAWAN - Adillah Azzahra; Astuti; Zulfah; Kasman Ediputra; Molly Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low interest in learning mathematics of class VIII students of MTs Muhammadiyah Penyasawan. This study aims to determine whether or not there is an influence of the Game Based Learning learning model using Baamboozle media on the learning interest of class VIII students of MTs Muhammadiyah Penyasawan. This research is a quasi-experimental study, with the sample technique used being Total Sampling. The population in this study were class VIII students of MTs Muhammadiyah Penyasawan in the 2024/2025 Academic Year consisting of 2 classes. The samples in this study were class VIII B as the control class and VIII A as the experimental class. The instruments used in this study were learning observation sheets and student learning interest questionnaire sheets. The data analysis techniques used were the Independent sample T-Test and the N-Gain test with the help of SPSS software. The results of the Independent sample T-Test obtained a T count of 3.902 with a significance of 0.000. Furthermore, the T table value was 2.004, where the hypothesis testing produced the T count test criteria> T table and sig. (2-tailed) < 0.05 concludes that H0 is rejected and there is an influence of the GBL learning model using Baamboozle media on the learning interests of students at MTS Muhammadiyah Penyasawan.